Effect of lipid sources on fatty acid profiles of meat from pasture- and feedlot-finished Nellore bulls - Fiorentini, G. [UNESP] (2018)
We aimed to compare the influence of two lipid sources (soybean grain [SG], and protected fat [PF, Lactoplus], based on soybean oil) with a control diet (no lipid supplementation) on the fatty acid (FA) profile (longissimus muscle and subcutaneous fat) of beef cattle finished on grazing pasture or at a feedlot. The study was arranged in a complete randomized design, using 2 × 3 factorial scheme that combined 2 finishing systems and 3 diets. Seventy-eight young Nellore bulls (323.8 ± 25.4 kg body weight [BW] and 21 ± 3 months of age) were divided at random into two finishing systems: 1) pasture-finishing and 2) feedlot-finishing. The diet containing PF increased CLA in the muscle (P = 0.0002). Pasture-finished bulls fed lipid-supplemented diets had significantly more (P = < 0.0001) subcutaneous saturated fatty acids and polyunsaturated fatty acids (PUFA) in muscle, whereas the PUFA concentration of PF-fed bulls was highest (P = < 0.0001) in subcutaneous fat. The highest (P = 0.0090) concentration of Omega-6 (n6) was observed in the muscle tissue of pasture-finished animals supplemented with SG. However, the lowest concentration (P = 0.0010) of n6 FAs in subcutaneous fat was more evident in pasture-finished animals receiving the control diet. The concentration of C20:5 n3 (EPA) was significantly higher (P = 0.040) in the muscle tissue of animals receiving the control diet in pasture and deposition of EPA was greater (P = 0.0020) in the subcutaneous fat of pasture-finished animals. The highest concentrations (P = < 0.0001) of n3 were observed in the muscle tissue of pasture-finished animals. Animals receiving the control diet in both finishing systems had a lower (P = 0.0051) n6:n3 ratio in muscle tissue. By comparison, feedlot-finished animals showed a higher (P < 0.01) n6:n3 ratio in muscle tissue, and the highest (P = 0.0190) n6:n3 ratio in subcutaneous fat was observed in pasture- and feedlot-finished animals supplemented with PF compared to the control diet. The muscle and subcutaneous fat tissues of feedlot-finished bulls fed the control and SG diets had a significantly higher (P < 0.05) Δ9-desaturase C16 index. The lowest (P = 0.0010) elongase concentrations were observed in the muscle tissue of PF-fed bulls, regardless of finishing system. Overall, bulls finished on grazing pasture had a more desirable FA composition.